The Effect of Person Job Fit and Work Autonomy on Innovative Behavior of Media Workers in Cirebon - Sari Aulia Rahma; Indra Darnah (PT FORMOSA CENDEKIA GLOBAL, 2025)
Creativity, innovation, and expertise are widely recognized as important competitive advantages that greatly enhance the survival and efficiency of organizations in a corporate environment. In this case, appropriate person job fit and job autonomy can drive employee innovation, which in turn drives competitive advantage in today's changing business environment. The study aims to analyze the extent to which independent variables influence the dependent variable. By collecting data and conducting analysis, this study contributes to how person job fit and job autonomy can influence the increase in innovative behavior of employees. The hypothesis is derived theoretically and then tested empirically using statistical analysis with a quantitative study of 130 respondents working in media companies in Cirebon. The results of the study indicate that there is an influence between person job fit and employee innovative behavior. Furthermore, the results of the study also reveal that job autonomy also influences innovative behavior.